Digital Transformation: The Role of Social Media in Strengthening Gender Inclusion in Contemporary Public Spaces - Nisa, Nur Khoirun; Khoironi, Nurul Kamilatul; Mutholingah, Siti (Journal Of Gender, Child And Humanity Studies, 2023)
Digital transformation through social media has opened new spaces for gender inclusion in the contemporary era. This research explores the role of social media in promoting gender equality and participation through a literature study method with a qualitative approach. By analyzing scientific sources from online academic platforms, this research examines how social media transforms social dynamics, gives voice to marginalized groups, and creates a more democratic public space. The research results show that social media has significant potential in deconstructing gender stereotypes, opening cross-border access to knowledge, and creating global advocacy networks. However, this research also identifies challenges such as digital violence, algorithmic bias, and the technology access gap. This study offers strategies to optimize the role of social media in achieving gender inclusion, including enhancing digital literacy, strengthening regulations, and multi-stakeholder collaboration.